Dynamic measurement of surface strain distribution on the foot during walking. (May 2017) - Ito, Kohta; Maeda, Kosuke; Fujiwara, Ikumi; Hosoda, Koh; Nagura, Takeo; Lee, Taeyong; Ogihara, Naomichi
Abstract: To clarify the mechanism underlying the development of foot disorders such as diabetic ulcers and deformities, it is important to understand how the foot surface elongates and contracts during gait. Such information is also helpful for improving the prevention and treatment of foot disorders. We therefore measured temporal changes in the strain distribution on the foot surface during human walking. Five adult male participants walked across a glass platform placed over an angled mirror set in a wooden walkway at a self-selected speed and the dorsolateral and plantar surfaces of the foot were filmed using two pairs of synchronized high-speed cameras. Three-dimensional (3D) digital image correlation was used to quantify the spatial strain distribution on the foot surface with respect to that during quiet standing. Using the proposed method, we observed the 3D patterns of foot surface strain distribution during walking. Large strain was generated around the ball on the plantar surface of the foot throughout the entire stance phase, due to the windlass mechanism. The dorsal surface around the cuboid was stretched in the late stance phase, possibly due to lateral protruding movement of the cuboid. It may be possible to use this technique to non-invasively estimate movements of the foot bones under the skin using the surface strain distribution. The proposed technique may be an effective tool with which to analyze foot deformation in the fields of diabetology, clinical orthopedics, and ergonomics.